System forensics, investigation, and response, second edition - Easttom, Chuck; Vacca, John R. (Burlington, MA : Jones & Bartlett Learning, 2014)
This completely revised and rewritten second edition begins by examining the fundamentals of system forensics, such as what forensics is, the role of computer forensics specialists, computer forensic evidence, and application of forensic analysis skills. It also gives an overview of computer crimes, forensic methods, and laboratories. It then addresses the tools, techniques, and methods used to perform computer forensics and investigation. Finally, it explores emerging technologies as well as future directions of this interesting and cutting-edge field. New and key features include: examination of the fundamentals of system forensics; discussion of computer crimes and forensic methods; incorporation of real-world examples and engaging cases. --
Rev. ed. of System forensics, investigation, and response / John R. Vacca and K. Rudolph. c2011.
Title from title screen.
Includes bibliographical references and index.
Keywords: Computer crimes -- Investigation; Forensic engineering; Electronic books